Affordability, financial innovation, and the start of the housing boom - Jane K. Dokko; Benjamin J. Keys; Lindsay E. Relihan (Federal Reserve Bank of Chicago, 2019)
At their peak in 2005, roughly 60 percent of all purchase mortgage loans originated in the United States contained at least one non-traditional feature. These features, which allowed borrowers easier access to credit through teaser interest rates, interest-only or negative amortization periods, and extended payment terms, have been the subject of much regulatory and popular criticism. In this paper, we construct a novel county-level dataset to analyze the relationship between rising house prices and non-traditional features of mortgage contracts. We apply a break-point methodology and find that in housing markets with breaks in the mid-2000s, a strong rise in the use of non-traditional mortgages preceded the start of the housing boom. Furthermore, their rise was coupled with declining denial rates and a shift from FHA to subprime mortgages. Our findings support the view that a change in mortgage contract availability and a shift toward subprime borrowers helped to fuel the rise of house prices during the last decade.
Keywords: 330